Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

The problem says: Suppose that $X$ and $Y$ are independent Poisson random variables with parameters 1 and 2 respectively. Find: $$\Bbb P (X=1|\frac{X+Y}{2} = 2)$$ I have thought about this for a long time and I thought that since $X$ and $Y$ are independent we could make it say $$\Bbb P(X=1|Y=4-2)=\frac{\Bbb P(X=1) \Bbb P(Y=4-X)}{\Bbb P(Y=4-X)}=\Bbb P(X=1)$$ however, I realize that $X$ and $Y$ are not independent that way. What am I doing wrong? I know this cant be that trivial but something isn't making sense to me.

share|cite|improve this question
up vote 2 down vote accepted

$$\Bbb P \left(X=1|\frac{X+Y}{2} = 2\right) = \Bbb P (X=1|{X+Y}= 4) $$

$$= \frac{\Bbb P \left(X=1 \text{ and } X+Y=4\right)}{\Bbb P \left(X+Y=4\right)}= \frac{\Bbb P \left(X=1 \text{ and } Y=3\right)}{\Bbb P \left(X+Y=4\right)} = \frac{\Bbb P (X=1) \Bbb P (Y=3) }{\Bbb P \left(X+Y=4\right)}$$

$$= \tfrac{\Bbb P (X=1) \Bbb P (Y=3) }{\Bbb P (X=0) \Bbb P (Y=4) + \Bbb P (X=1) \Bbb P (Y=3) +\Bbb P (X=2) \Bbb P (Y=2)+\Bbb P (X=3) \Bbb P (Y=1)+\Bbb P (X=4) \Bbb P (Y=0)}$$

which you can calculate.

share|cite|improve this answer
Let me mention that the denominator is P(Z=4) for Z Poisson with parameter 1+2=3, hence it equals e^(-3)3^4/4! (which might be simpler than the summation of five products). The exponentials cancel out hence one is left with (1^1/1!)(2^3/3!)(4!/3^4)=32/81. – Did Oct 30 '12 at 23:06

Recall that $$P(A \vert B) = P(A \cap B)/P(B) = P(B/A) \times P(A)/P(B)$$ Hence, $$P(X = 1 \vert X+Y = 4) = P(X+Y=4 \,\,\& \,\, X=1)/P(X+Y = 4)$$ So we need to evaluate is $P(X+Y=4 \,\,\& \,\, X=1)$ and $P(X+Y = 4)$ $$P(X+Y=4 \,\,\& \,\, X=1) = P(X=1 \,\,\& \,\, Y=3) = P(X=1)P(Y=3)$$ $$P(X+Y = 4) = \sum_{k=0}^4P(X=k)P(Y=4-k)$$

share|cite|improve this answer
The sum at the end is not useful, see my comment on the other answer. – Did Oct 30 '12 at 23:12
@did True. But the way I would have gone about simplifying is to multiply and divide by $4!$, which would have given $e^-(1+2) (1+2)^4/4!$. (essentially proving that sum of two poisson is again possion) – user17762 Oct 30 '12 at 23:15

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.